Technology and medical practice : blood, guts and machines - Johnson, Ericka, 1973-; Berner, Boel. (Farnham, England ; Burlington, VT : Ashgate, 2010)
"Modern medicine is highly technological, with advanced technologies being used in diagnosis and care to provide knowledge about the patient, define bodily states and structure everyday medical interventions and divisions of labour. Whilst supporting and making medical practices possible, however, their design and use may also conflict with established traditions of medicine and care. What happens to the patient in a technologized medical environment? How are doctors', nurses' and medical scientists' practices changed when artefacts are involved? How is knowledge negotiated, or relations of power reconfigured?" "Technology and Medical Practice addresses these developments and dilemmas, focusing on various practices with technologies within hospitals and sociotechnical systems of care. Technologies are discussed as part of the sociotechnical environment of everyday medical practices, alongside the emotions of trust and distrust, fear, relief and compassion which they involve." "Combining science and technology studies with medical sociology, the history of medicine and feminist approaches to science, this book presents analyses of artefacts-in-use across a variety of settings within the UK, USA and Europe, and will appeal to sociologists, anthropologists and scholars of science and technology alike."--BOOK JACKET.
Includes bibliographical references and index.
boek